Affective well-being in the higher education sector: connecting work-life balance with mental health, job satisfaction and turnover intention issues inside the academia setting. (28th October 2019) - Badri, S.K.Z.
At present, well-being remains as an important topic that is constantly discussed in the academia setting. Intense technological revolution and changes in administration, approaches as well as job characteristics have increased the need for thorough well-being administration among workers in higher education sectors, especially among academics as they serve as the backbone of higher education system. That said, this paper investigated the well-being conditions of academics through the lenses of their work-life balance. To address this proposition, a total of 307 academics were observed, whereby their conditions of well-being were investigated by evaluating their mental health, job satisfaction and turnover intention. This study utilised a quantitative approach, using a self-administered survey as the data collection tool. Results obtained pointed out two important patterns, one of which was that poor work-life balance was connected to poor condition of mental health, lower job satisfaction and higher turnover intention. In contrary, great work-life balance was linked with good mental health condition, higher job satisfaction and lower turnover intention. Discussion drawn from this paper highlighted the significance and twofold effects of work-life balance in affecting academics' well-being, which will in turn benefit future researchers, human resource practitioners and academics itself.